Testicular atrophy following paediatric primary orchidopexy: A prospective study. Issue 4 (August 2016) - Durell, J.; Johal, N.; Burge, D.; Wheeler, R.; Griffiths, M.; Kitteringham, L.; Stanton, M.; Manoharan, S.; Steinbrecher, H.; Malone, P.; Griffin, S.J.
Summary: Background: With the Nordic consensus statement advocating orchidopexy at an earlier age, the present study sought to investigate the outcomes of primary paediatric orchidopexy at a tertiary UK centre. Objective: To prospectively assess testicular atrophy following primary orchidopexy for undescended testes in a paediatric population. Secondary outcomes were complication rates and whether outcomes were dependent on grade of operating surgeon. Study design: Prospective data regarding age at operation, classification of the undescended testis, length of follow-up, and subjective comparison of intraoperative and postoperative testicular volumes compared with the contralateral testis were collected. Testicular atrophy was defined as >50% loss of testicular volume or a postoperative testicular volume <25% of the volume of the contralateral testis. Patients were excluded for incomplete data and follow-up <6 months. Results: Data for 234 patients were analysed. Testicular atrophy occurred in 2.6% of cases. There was no reported testicular re-ascent. All secondary acquired cases underwent a previous ipsilateral hernia repair. There was no significant difference in outcomes comparing the grade of surgeon (consultant n = 8, trainee/staff-grade surgeon n = 7–8). There was a trend towards postoperative catch-up growth in approximately one fifth of cases. Discussion: Previous studies have reported a testicular atrophy rate of 5%. The present study reported a similar rate of 2.6%. In agreement with a previous publication, it was also found that testicular atrophy was not dependent on the grade of operating surgeon. The mechanism for testicular catch-up growth is not well understood. Animal studies have supported the hypothesis that increased temperature has a detrimental effect on testicular volume. However, follow-up in the present cohort was short (median 6.9 months), making interpretation of this finding difficult. It is acknowledged that clinical palpation alone to determine testicular volume potentially introduces intra-observer and inter-observer error. However, prospective studies using ultrasound to determine testicular volumes following orchidopexy have reported catch-up growth. Conclusion: This study represented one of the larger collections of prospective assessments of outcomes following primary orchidopexy. It was acknowledged that subjectively assessing testicular volume is not ideal; however, the data correlated with similar studies. Table Testicular atrophy grouped by aetiology of undescended testis. Aetiology of undescended testis Age at operation, years (median) Length of follow-up, months (median) Testicular atrophy rate Overall (n = 234) 2.2 6.9 6 (2.6%) Congenital (n = 209) 1.8 7.1 6 (2.9%) Primary acquired (n = 21) 8.7 6.5 0% Secondary acquired (n = 4) 4.5 6.4 0%